Spectrophotometic Determination of Isoniazid (INH) Using 2,4-dinitro-1-flourobenzene (DNFB) - Application to Tablet - Hayfa M. Jassim Al-Hammoshi (College of Education for Pure Sciences, 2012)
Abstract A rapid, simple, reproducible and sensitive spectrohpotometric method for assay of (INH) was investigated. The method is based on the reaction of INH with 2,4-dinitro-1-flourobenzene reagent to give a highly colored species with maximum at λ 428 nm in aqueous medium of pH 10.3. Beer's law was obeyed in the range of (0.05 - 2.5) µg/ml with a molar absorptivity 2.7 x 104 l.mol l-1 cm-1 .The sandell index was 0.005 µg.cm-2 and the limit of detection was 0.00984 µg/ml. The accuracy (average recovery%) was 99.99% and the relative standard deviation (RSD) was better than ±1.0%. Also it was found that the product formed was in a ratio of 1:1 with a stability constant of 5.9 x 103 l.mol-1. The method was applied successfully to assay INH in pharmaceutical formulations and agreed well with its certified value and the British pharmacopoeia method.